DISSEMINATED DLE PROGRESSING TO SLE- A CASE REPORT (Journal of Pharmaceutical Negative Results, 2022)
Lupus erythematosus is an autoimmune disease with a clinical spectrum ranging from mild cutaneous lesions to life-threatening diseases like nephritis, serositis and CNS involvement. James N. Gilliam developed a classification for LE-specific lesions which was divided into Acute cutaneous lupus erythematosus (ACLE), Subacute cutaneous lupus erythematosus (SCLE), chronic cutaneous lupus erythematosus (CCLE). The most common subset of chronic cutaneous lupus erythematosus is DLE. Most patients with DLE do not have significant systemic disease. The risk of developing SLE is 20% in disseminated DLE versus 5% in the localized form. Here we report a 41-year-old female patient who was a known case of DLE presentedwith history of new skin and mucosal lesions, fever, and joint pain. On further investigation, it was found that the patient has progressed to SLE. Careful history-taking , clinical examination and complete investigations should be carried in DLE patients to rule out progression to SLE.